Analysis of infant mortality on the borders of the Southern Arc of Brazil, 2010-2020 (Research, Society and Development, 2023)
Infant mortality constitutes a serious public health problem and is closely linked to inequities in access to health and the quality of care provided to mother and child. This research aimed to analyze infant mortality in the border municipalities of Arco Sul do Brasil, in the period 2010-2020. This is a descriptive study with a quantitative approach in the 56 municipalities on the border of the states of Paraná, Santa Catarina and Rio Grande do Sul, carried out through the collection of secondary data from the Mortality Information System and the Birth Information System Vivos, in which some maternal and child variables were extracted and, after collection, the data were analyzed and tabulated in Microsoft Office Excel spreadsheets. As a result, it was identified that the border municipalities of the analyzed states had higher Infant Mortality Rates than those of their respective states, with emphasis on the border of Rio Grande do Sul, which had the most alarming Infant Mortality Rate. In relation to age group, the Early Neonatal Mortality Rate was the most epidemiologically relevant. It was concluded that the target proposed by the Sustainable Development Goals was not achieved, even with the decrease in infant mortality in the period analyzed. Therefore, it is still necessary to seek improvements in the accessibility and quality of healthcare for the border population.